O livro de emblemas de Andrea Alciato : apresentação e tradução - Sauka, Mariana Yelena [UNIFESP] (2016)
The present project proposes a presentation of the work of Andrea Alciato, Emblematum Libellus, or Book of Emblems, followed by a translation from Latin to Portuguese in the form of Appendix of the Paris edition, 1534. The emblematic production was originated in the Renaissance, through the publication of Alciato?s work, whose initial goal was to convey moralizing content to its readers. The emblems are composed by motto, engraving and epigram; and they have their production of meaning through the allegories resulting from this set. Besides the translation of the emblems, we add notes about relevant elements included in the work, such as references to Greek, Roman and Egyptian mythologies, to texts and characters of ancient and medieval literature, and the direct dialogue with the Greek Anthology, which was the basis for the writing of the first emblems. Moreover, we prepared a presentation for this work by comparing some of the most important editions of the Book (which reached approximately hundreds of editions and circulated throughout Europe), and also to justify the importance of research on this subject in Brazil, whose reflection occurred in Baroque, through the production of allegorical tiles, which dated back the proposal to teach. The results of this work will contribute to increase access to this little-known literature in our country, and also it may increase the interest for research on the subject, since this type of production is very productive for studies in various aspects.